Intervensi Pratek Lapangan Bidang Psikologi Industri Dan Organisasi Di Rumah Sakit Columbia Asia Medan - Elsa Grace Cintya Harianja; Nenny Ika Putri Simarmata; Nancy Naomi (Journal on Education, 2023)
Students are one of the human resources who will later enter the world of work and must adapt and be able to develop themselves to the environment they will face after graduating from college by equipping themselves with education and skills (soft skills and hard skills). In order to produce a workforce that is reliable and professional in their fields, universities are required to prepare their graduates well in implementing the knowledge they have learned in improving human resources (HR). From the results of interviews conducted by the author to the four staff, it is known that the have problems related to team performance. This statement can be supported from complaints that have been submitted by staff that the contribution made by each individual in the team is very minimal, such as in terms of giving arguments/opinions/ideas to problems in the room. The purpose of this study is to apply psychological principles related to carrying out data collection, diagnosis, prognosis, counseling and psychotherapy activities under the guidance of a psychologist. The main areas of study in this internship program include: educational psychology, social psychology, organizational industrial psychology, clinical psychology and developmental psychology. This research method conducted interviews and observations.